Development and Evaluation of Electronic Social Needs Assessment and Resource Connection Tool in Facilitating Utilization of Community Services That Address Upstream Health - Heather Farthing; Sarah Simko; Francelia J Eckembrecher; Daphne G Eckembrecher; Isabel Penabad; Yanelys Fernandez; Veronica Nunez; Sophia Pines; Nicole Cruz; Rebecca Tanenbaum; Berta Cabrera; Luz Gallardo; et al. (Journal of Student-Run Clinics, 2021)
Background: Social determinants of health (SDOH) put some groups who access care at student-run free clinics (SRFCs) at higher risk for adverse medical outcomes. Free or low-cost community services supplement clinic-based interventions, but access is limited by knowledge, transportation, language, and/or trust. Social needs assessments may be electronically paired with resource connection tools to connect patients to local, validated resources. The objective of this pilot study was to evaluate the SDOH screen and resource connection tool developed at a SRFC.Methods: The tool was piloted with a convenience sample of 40 patients with scheduled outpatient appointments at a SRFC in Miami, Florida. Participants were given information about a variety of services and screened for high-risk situations such as human trafficking. Follow-up survey via telephone at 2-4 weeks identified survey acceptability, successful connections, and barriers to access.Results: Forty participants completed the assessment. All participants were counseled regarding exercise and nutrition and requested information about more than one resource. Sixty percent (n=24) were successfully contacted for follow-up. Of these, 29% (n=7) were able to connect with one or more recommended resources. Reasons given for failure to access resources included lack of time or transportation, health issues, and lack of response from contacted organizations.Conclusions: Social needs assessments may be implemented in SRFCs to identify high-risk needs, facilitate linkage to local organizations that meet these needs, gather data to guide future programming, and provide education and counseling. Stronger connections with local organizations and closed loop referrals may be needed to facilitate connection to community resources.